Facile preparation of sisal–Fe/Zn layered double hydroxide bio-nanocomposites for the efficient removal of rifampin from aqueous solution: kinetic, equilibrium, and thermodynamic studies. Issue 5 (16th April 2023) - Negarestani, Mehrdad; Farimaniraad, Hamidreza; Mollahosseini, Afsaneh; Kheradmand, Asiyeh; Shayesteh, Hadi
Abstract: In the present study, sisal–Fe/Zn LDH bio-nanocomposite for efficiently removing rifampin was synthesized using a simple co-precipitation method. SEM, XRD, and FTIR analyses were applied to characterize the prepared composite. In the following, different factors that are affecting the adsorption of rifampin, including contact time, initial rifampin concentration, adsorbent dosage, and temperature were evaluated. Also, the kinetic, isotherm, and thermodynamic studies were investigated. The results indicated that Freundlich ( R 2 = 0.9976) was a suitable model for describing the adsorption equilibrium and adsorption kinetic showed that the data are in maximum agreement with the pseudo-second-order kinetic model ( R 2 = 0.9931). According to the Langmuir isotherm model, the maximum adsorption capacity of rifampin was found to be 40.00 mg/g. The main mechanisms for rifampin elimination were introduced as electrostatic attraction and physical adsorption. Moreover, the spontaneity and nature of the reaction were analyzed by elucidating thermodynamic factors that indicated the adsorption process was exothermic and spontaneous. Also, the batch process design indicated that for treating 10 L wastewater containing 100 mg/L rifampin with a removal efficiency of 96%, the needed amount of sisal–Fe/Zn LDH is 51.6 g. This study revealed that the sisal–Fe/Zn LDH bio-nanocomposites as a low-cost adsorbent have promising adsorption potential. Novelty statement: In this study, an innovative bio-nanocomposite (sisal–Fe/Zn layered double hydroxide) has been synthesized using a co-precipitation method for the first time and was used for the removal of pharmaceutical pollutants. Sisal–Fe/Zn LDH exhibited an excellent adsorption capacity of 40.00 mg/g to remove rifampin from the aqueous solution. The main mechanisms for rifampin elimination were introduced as electrostatic attraction and physical adsorption. Also, the batch process design showed that for treating 10 L wastewater containing 100 mg/L rifampin with a removal rate of 96%, the amount of sisal–LDH bio-nanocomposite required is about 51.6 g. Therefore, sisal–Fe/Zn layered double hydroxide as an eco-friendly biosorbent can be considered for future water treatment. Graphical Abstract: UF0001